2022
DOI: 10.3390/ma15165753
|View full text |Cite
|
Sign up to set email alerts
|

Change of the Structural Properties of High-Performance Concretes Subjected to Thermal Effects

Abstract: The paper refers to studies of the structure of high-performance concrete with polypropylene fibre at different dosages. The authors see a research gap in the study of the effect of adding polypropylene fibre on the parameters of concrete exposed to high temperatures. The study takes into account the thermal effect—groups of samples were heated to 200 °C, 400 °C and 600 °C. The authors carried out basic tests to describe the changes in density, ultrasonic tests, uniaxial compression strength tests and tensile … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…In the existing studies, SCC meeting special combinations of performance and uniformity requirements that cannot always be achieved routinely by using conventional concrete is generally considered as high-performance concrete (HPC) [19][20][21]. Moreover, some remarkable conclusions showed that the mechanical properties of HPC, which can be obtained from the available bibliography [22,23]. When the HPC specimens were continuously heated in fires, because of the dense internal microstructure, the spalling gradually became severe, which made it difficult to transport and release the water vapor inside the concrete.…”
Section: Test Specimensmentioning
confidence: 99%
“…In the existing studies, SCC meeting special combinations of performance and uniformity requirements that cannot always be achieved routinely by using conventional concrete is generally considered as high-performance concrete (HPC) [19][20][21]. Moreover, some remarkable conclusions showed that the mechanical properties of HPC, which can be obtained from the available bibliography [22,23]. When the HPC specimens were continuously heated in fires, because of the dense internal microstructure, the spalling gradually became severe, which made it difficult to transport and release the water vapor inside the concrete.…”
Section: Test Specimensmentioning
confidence: 99%
“…Nowadays, the aspect of concrete durability, including its resistance to weather and chemical conditions, is widely discussed in the literature [30,46,48], which justifies the requirements formulated in the standard with regard to ensuring the durability of implemented concrete structures. Other research directions are environmental awareness in concrete production [18], including the use of recycled materials [14] and innovations in concrete technology, such as high-value, rolled concrete, are opening up new opportunities for the construction industry [33]. A new research direction is the use of advanced modelling tools to predict the behaviour of concrete [9,23] or simulation, probabilistic or statistical methods in the evaluation of requirements or quality control procedures [44].…”
Section: Introductionmentioning
confidence: 99%
“…These results provide valuable references for sand stabilization via cementation. In another investigation into high-performance polypropylene fiber-reinforced concrete (HPFRC) under the effect of high temperature conditions of 200, 400, and 600 • C, Kaczmarczyk et al [2] reported that at high temperatures, the enhanced properties of HPFRC were not obvious due to the complete melting of the polypropylene fibers. However, the melting of polypropylene fibers could provide free space to reduce pore pressure, which caused a delay in the development of micro-cracks in the HPFRC structure, and the little change in the HPFRC structure could increase the heat resistance of concretes.…”
mentioning
confidence: 99%